Tenho um Galante Chinelo: Sapateiro Silva, a pobreza, a sátira e o anfiguri - Coelho, Assíria Leite (2024)
The present study aims to analyze the literary work of the poet Sapateiro Silva. Regarding his biography, all that remains are a few traces that together provide scant clues about his history: Joaquim José da Silva was a poet from Rio de Janeiro who lived at the turn of the 18th to the 19th century, and as his artistic name suggests, he was formally a shoemaker (Candido, 2000). Silva's work consists in seven glosses and eight sonnets, and his poetry differs in several aspects from the nineteenth-century writing, which primarily dealt with ideological issues linked to the interests of cultured literati in colonial Brazil. The author's poetic narration focuses on the impoverished life in Rio de Janeiro in the early 19th century, thus proposing a socially inverted perspective: from within to without. His work also stands out for its satirical and modern character, anticipating several trends later adopted by other poets. The research is justified by the lack of existing studies dedicated to the analysis of Sapateiro Silva's poems. As for specific objectives, the analysis was conducted focusing on (1) the characteristics of poverty representation in his texts and (2) satire as a constructive element of his writing. To provide theoretical grounding, we refer to the study by Flora Sussekind and Rachel Valença titled "O Sapateiro Silva" (1983), through which the writer was rediscovered in academic circles. Regarding poverty in his literature, insights from Michel de Certeau (1998) on the "ordinary man" and Gilles Deleuze and Félix Guattari's text "Kafka: Toward a Minor Literature" (2014[1975]) are considered. For satire, the discussion draws from texts by critic Ricardo Domeneck and the thoughts of Eduardo Aguirre Romero (2018).